Participation in the Divine: The Method and Content of the Religious Epistemology of Jonathan Edwards - Steffaniak, Jordan L. (Jonathan Edwards studies, 2019)
This essay will define the religious epistemology of Jonathan Edwards by way of method and content. The method of epistemology for Edwards will be sketched within the framework of his metaphysical idealistic phenomenalism. The content of his epistemology will be defined as divine communication of fullness. In this he blends Eastern and Western elements to construct his view